Human resource strategies and employees' job satisfaction in the public sector a study of two cases - Ligon, Deborah B
In an effort to evaluate the existing HR practices in the public sector and how they influence the feelings of satisfaction in the job of the employees, two agencies of the Department of Agriculture were investigated. The study also aimed to determine the work values and career needs of the employees that they may influential in their idea of an ideal HR. Using one-on-one and group interviews, 41 rank and file employees (employee's perspective) and 2 HR Chiefs (management's perspective) participated in this exploratory case research. The overall results show that both agencies have not been remiss in providing opportunities that would fulfill some of the employees' important work values and needs which appear to be centered on professional growth and development. However, the employees do find their HR lacking in the aspects of proper policy implementation, a requirement they find in an ideal HR. As for the feeling of satisfaction, by and large, the employees manifest a fairly high level of satisfaction in the job, attributing to 43% of their feelings to satisfaction to HR services and provisions while the rest to the general working environment, their colleagues and peers and the nature of their respective jobs.